Identitas Gaya Fesyen Islami pada Sivitas Akademika di Perguruan Tinggi Kota Semarang (Identity of Islamic Fashion among Academic Staffs at Higher Education in Semarang City) - Arni Ernawati; Erna Zuni Astuti; Teguh Hartono Patriantoro; Rustono Farady Marta; Jouns Candy Felice Lang (Jurnal Dakwah Risalah, 2020)
Identity characterizes each individual, especially for scholars, both lecturers, and students. This study aims to explore the identity of Islamic fashion styles within the scope of higher education in the city of Semarang. This research uses a qualitative approach with a case study method. The research informants consisted of four lecturers and four students at private and public campuses in the city of Semarang. The findings of this study indicate that one way to express an identity for muslim scholars to use islamic clothing or clothing. Clothing has now gone beyond its function to protect the body but has become a means of communication that can express one's identity. With the development of the times, clothing also has a role that changes with time. Now islamic fashion is a necessity for muslim scholars to follow trends while maintaining self-respect and covering their aurat (i.e. body parts required by Islam to be covered).